Second Paediatric Strategy Forum for anaplastic lymphoma kinase (ALK) inhibition in paediatric malignancies: ACCELERATE in collaboration with the European Medicines Agency with the participation of the Food and Drug Administration. (November 2021) - Pearson, Andrew D.J.; Barry, Elly; Mossé, Yael P.; Ligas, Franca; Bird, Nick; de Rojas, Teresa; Zimmerman, Zachary F.; Wilner, Keith; Woessmann, Willi; Weiner, Susan; Weigel, Brenda; Venkatramani, Rajkumar; et al.
Abstract: The first (2017) and sixth (2021) multistakeholder Paediatric Strategy Forums focused on anaplastic lymphoma kinase (ALK) inhibition in paediatric malignancies. ALK is an important oncogene and target in several paediatric tumours (anaplastic large cell lymphoma [ALCL], inflammatory myofibroblastic tumour [IMT], neuroblastoma and hemispheric gliomas in infants and young children) with unmet therapeutic needs. ALK tyrosine kinase inhibitors have been demonstrated to be active both in ALK fusion-kinase positive ALCL and IMT. ALK alterations differ, with fusions occurring in ALCL, IMT and gliomas, and activating mutations and amplification in neuroblastoma. While there are many ALK inhibitors in development, the number of children diagnosed with ALK driven malignancies is very small. The objectives of this ALK Forum were to (i) Describe current knowledge of ALK biology in childhood cancers; (ii) Provide an overview of the development of ALK inhibitors for children; (iii) Identify the unmet needs taking into account planned or current ongoing trials; (iv) Conclude how second/third-generation inhibitors could be evaluated and prioritised; (v) Identify lessons learnt from the experience with ALK inhibitors to accelerate the paediatric development of other anti-cancer targeted agents in the new regulatory environments. There has been progress over the last four years, with more trials of ALK inhibitors opened in paediatrics and more regulatory submissions. In January 2021, the US Food and Drug Administration approved crizotinib for the treatment of paediatric and young adult patients with relapsed or refractory ALCL and there are paediatric investigation plans (PIPs) for brigatinib and for crizotinib in ALCL and IMT. In ALCL, the current goal is to investigate the inclusion of ALK inhibitors in front-line therapy with the aim of decreasing toxicity with higher/similar efficacy compared to present first-line therapies. For IMT, the focus is to develop a joint prospective trial with one product in children, adolescents and adults, taking advantage of the common biology across the age spectrum. As approximately 50% of IMTs are ALK -positive, molecular analysis is required to identify patients to be treated with an ALK inhibitor. For neuroblastoma, crizotinib has not shown robust anti-tumour activity. A focused and sequential development of ALK inhibitors with very good central nervous system (CNS) penetration in CNS tumours with ALK fusions should be undertaken. The Forum reinforced the strong need for global academic collaboration, very early involvement of regulators with studies seeking possible registration and early academia-multicompany engagement. Innovations in study design and conduct and the use of 'real-world data' supporting development in these rare sub-groups of patients for whom randomised clinical trials are not feasible are important initiatives. A focused and sequenced development strategy, where one product is evaluated first with other products being assessed sequentially, is applicable for ALK inhibitors and other medicinal products in children. Highlights: ALK is an important oncogene and target in several paediatric tumours. There are many ALK inhibitors but a small number of children with ALK malignancies. Focused and sequential development of ALK inhibitors is required. There are now more trials of ALK inhibitors and regulatory submissions than in 2017.